Successful integration of newborn genetic testing into UK routine screening using prospective consent to determine eligibility for clinical trials. Issue 1 (28th September 2022) - Bendor-Samuel, Owen Martyn; Wishlade, Tabitha; Willis, Louise; Aley, Parvinder; Choi, Edward; Craik, Rachel; Mujadidi, Yama; Mounce, Ginny; Roseman, Fenella; De La Horra Gozalo, Arancha; Bland, James; Taj, Nazia; et al.
Abstract : Objective: INGR1D (INvestigating Genetic Risk for type 1 Diabetes) was a type 1 diabetes (T1D) genetic screening study established to identify participants for a primary prevention trial (POInT, Primary Oral Insulin Trial). Methods: The majority of participants were recruited by research midwives in antenatal clinics from 18 weeks' gestation. Using the NHS Newborn Bloodspot Screening Programme (NBSP) infrastructure, participants enrolled in INGR1D had an extra sample taken from their day 5 bloodspot card sent for T1D genetic screening. Those at an increased risk of T1D were informed of the result, given education about T1D and the opportunity to take part in POInT. Results: Between April 2018 and November 2020, 66% of women approached about INGR1D chose to participate. 15 660 babies were enrolled into INGR1D and 14 731 blood samples were processed. Of the processed samples, 157 (1%) had confirmed positive results, indicating an increased risk of T1D, of whom a third (n=49) enrolled into POInT (20 families were unable to participate in POInT due to COVID-19 lockdown restrictions). Conclusion: The use of prospective consent to perform personalised genetic testing on samples obtained through the routine NBSP represents a novel mechanism for clinical genetic research in the UK and provides a model for further population-based genetic studies in the newborn. Abstract : This study looked at the use of prospective consent for participation in a study using the newborn screening blood spot to evaluate a genetic risk score for Type 1 Diabetes. This score was used to identify individuals who were offered an opportunity to participate in an interventional trial. The methodology provides a model for future clinically relevant population based genetic research.